Student Self-Regulation in Learning during Online Learning Judging from Self-Efficacy - Aulia, Tia Fahrina; Rifayanti, Rina; Rasyid, Miranti (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the correlation between self-efficacy and self-regulated learning in college students during online learning. This research method used a quantitative approach. The subjects in this study were 100 students of the Faculty of Social and Political Sciences, Mulawarman University who were selected using a random sampling technique. The data collection method used is a self-efficacy scale and self-regulated learning scale. The results showed that there was a significant positive correlation between self-efficacy and self-regulated learning in college students during online learning with a calculated r value of 0.474 > r table 0.197 and a sig of value of 0.000 (p < 0.05), which indicates, the higher the self-efficacy, the higher self-regulated learning in college students during online learning.Penelitian ini bertujuan untuk mengetahui hubungan antara efikasi diri dengan regulasi diri dalam belajar selama pembelajaran daring pada mahasiswa. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek dalam penelitian ini adalah 100 mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman yang dipilih dengan menggunakan teknik random sampling. Metode pengumpulan data yang digunakan adalah dengan skala efikasi diri dengan skala regulasi diri dalam belajar. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara efikasi diri dengan regulasi diri dalam belajar selama pembelajaran daring pada mahasiswa dengan nilai r hitung 0.474 > r tabel 0.197 dan nilai sig 0.000 (p < 0.05), yang artinya bahwa semakin tinggi efikasi diri, maka semakin tinggi pula regulasi diri mahasiswa dalam belajar selama pembelajaran daring.